Japanes Institute for Sports Sciences: Sports Information Service Program (2009)
JISS collects various information key to improving athletic performance. We process and compile the information, then distribute it to athletes, coaches and related staff. To this end, we manage information databases of Japanese sports and are working to build national and international sports information networks and promote greater cooperation to ensure greater availability of sports information. JISS also promotes the use of editing and processing technologies for game film analysis. We give presentations explaining how to use video editing equipment and open our Sports Information Service facilities to the public. JISS collects and compiles information on a wide range of topics. It follows domestic and international sports as well as social and economic trends; the latest trends in sports medicine and science, technologies, strategy, and tactics; and the training facilities of the worlds top athletes. Based on analysis of this information, coaches and trainers can devise effective methods that are key to improving the athletes performance.